Social Loafing and Impression Management in an Organizational Context - Meydan, Cem Harun; Kahraman, Cagdas Akif; Basar, Ufuk (International Review of Management and Marketing, 2014)
The aim of this study is to find out relationship between behaviors of people who tend to loaf in organizational context and their impression management strategies, and to reveal specific impression management strategies applied by loafers. Our research is conducted with voluntary participation of 100 bank clerks, who work at a private bank located in Ankara, Turkey. Data were collected by means of questionnaires. Findings indicate that social loafers are engaged in impression management strategies. Loafers, who feel disconnected, behave distractive and disruptive. However, perceived results of loafing curtail their face saving efforts. Findings are further discussed and recommendations for future studies are emphasized. Keywords: Social loafing; Impression management; Social loafer; Group; Behavior. JEL Classifications: D23; M12